Dictating the Risk: Experimental Evidence on Giving in Risky Environments: Reply - Brock, J. Michelle; Lange, Andreas; Ozbay, Erkut Y. (American Economic Review, 2016)
In Brock, Lange, and Ozbay (2013), we experimentally investigate social preferences under risk. One of our conclusions is that a social preference model incorporating both ex ante and ex post fairness concerns may best describe behavior. Krawczyk and Le Lec (2016 ) argue that ex ante comparisons alone may account for our data. We address their points in this reply. (JEL C72, D63, D64, D81)